An active transverse energy filter to differentiate low energy particles with large pitch angles in a strong magnetic field - Gauda, Kevin; Schneidewind, S.; Drexlin, G.; Fulst, A.; Hannen, V.; König, T.; Lokhov, A.; Oelpmann, P.; Ortjohann, H.-W.; Pernice, Wolfram; Robertson, R. G. H.; Salomon, R. W. J.; et al. (The European physical journal. C, Particles and fields, 2022)
We present the idea and proof of principle measurements for an angular-selective active filter for charged particles. The motivation for the setup arises from the need to distinguish background electrons from signal electrons in a spectrometer of MAC-E filter type. While a large fraction of the background electrons exhibit predominantly small angles relative to the magnetic guiding field (corresponding to a low amount of kinetic energy in the motion component transverse to the field lines, in the following referred to as transverse energy) and pass the filter mostly unhindered, signal electrons from an isotropically emitting source interact with the active filter and are detected.